UPAYA PENINGKATAN PEMAHAMAN KONSEP PESERTA DIDIK KELAS V PADA MATERI SISTEM PEREDARAN DARAH MELALUI MODEL PEMBELAJARAN WINDOWS SHOPPING BERBANTUAN VIDEO ANIMASI - Hikmah; Fatimah; Fatma Zuhra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by students’ low conceptual understanding, limited participation in the learning process, and low student responses in the Natural and Social Sciences (IPAS) subject in Grade V at UPTD SD Negeri 4 Peusangan. The study aimed to determine the improvement of students’ conceptual understanding, teacher and student activities, and student responses through the implementation of the Window Shopping learning model assisted by animated videos on the topic of the circulatory system. This study employed a qualitative approach using Classroom Action Research (CAR), which was conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The research subjects were 18 fifth-grade students. Data were collected through tests, observations, questionnaires, interviews, and field notes. Data analysis was carried out by calculating the percentages of learning mastery, teacher and student activities, and student responses. The results showed that the implementation of the Window Shopping learning model assisted by animated videos improved students’ conceptual understanding, as indicated by the increase in learning mastery from 66.7% in Cycle I to 88.9% in Cycle II. Teacher activity improved from the good category to the very good category, increasing from 76.3 to 96.3. Student activity also increased from 71.3 to 94.4, reaching the very good category. In addition, student responses to the learning process were highly positive, with 82.8% of students giving positive responses. Therefore, it can be concluded that the Window Shopping learning model assisted by animated videos is effective in improving students’ conceptual understanding, learning activities, and responses in IPAS learning at the elementary school level.